Penciptaan Manusia Menurut Pandangan Al-Qur’an (Konsep Ahsanu Taqwim Dalam Al-Qur’an Studi Tafsir Ibnu Katsir) - Yuslam A'yunin Nabilah; Salim Ashar; Abdul Holik (PT. Hasba Edukasi Mandiri, 2025)
Humans are basically one of the creatures created by Allah SWT with the best creation among other creatures of Allah, then Allah created humans along with the noble tasks they do. Islam explains that Allah SWT created humans from the ground and then became nutfah, 'alaqah and mudgah so that they finally became the most perfect creatures of Allah SWT and had various abilities. Allah SWT created man (ahsanu taqwim), which is the best creation and conquest of nature and its contents for humans so that humans can maintain, manage and preserve survival in this universe. This research uses a qualitative method with descriptive analysis, which aims to identify, classify, and interpret verses that discuss human creation. This research was raised to find out how the stages of human creation are in the Qur'an. The problem in this study is Imam Ibn Kathir's view about Ahsanu Taqwim, This research also discusses the backbone of Ahsanu Taqwim, namely the existence of humans who are born with defects, the background of why humans are created, the benefits and purposes of human creation. The results of this study are; The stages of human creation in the Qur'an are divided into 4, namely, from a drop of despicable semen, second: then after 40 days Allah makes it a clot of blood, third: then after 80 days in the phase of nutfah, alaqah, mudqhah He makes a lump of flesh into bony flesh. And the spirit was blown to the Fetus.